Foreword by the Editor-in-Chief - Nataliya Pasyechnikova (Ukrainian Society of Ophthalmologists, 2023)
Dear colleagues, On one of these days preceding a New Year celebration, you hold in your hands or read on your screen the last issue of the Journal of Ophthalmology (Ukraine) for the year 2023. Although the year that passes was very difficult and challenging for all of us, our authors' hard work and readers' interest allowed us not only to maintain, but also to keep raising the journal's academic level. At present, the journal is the only Ukrainian ophthalmological journal indexed by Scopus and cited in foreign publications. The English version of the journal is equivalent to its original Ukrainian version and is an ope-access journal which is integrated harmoniously into the current global fast-pace information environment. Our constant cooperation with our authors contributes to improved scientific quality of publications in the journal, which attracts the attention of foreign authors and international organizations. Our editorial staff's primary New Year's wish is peace! We wish victory for all of us! And we wish inspiration and advances in science for all our readers and colleagues! From our side, we will certainly be making extra effort in 2024 to select, process and publish high-quality science, and to improve our cooperation with authors and international cooperation. We are grateful to our authors, who despite current hardship, continue working and reporting on the results of their studies and interesting cases in ophthalmology. Our editorial staff would also like to express our gratitude to our dear reviewers - our work would be impossible without them! Merry Christmas and Happy New Year 2024! Let you live in peace and harmony, and let your dreams come true! Nataliya Pasyechnikova